Decision-Making In The Implementation Of Risk Management In A Logistics Forwarding Company: A Case Study Of PT NLO - Nurul Adilla; Desi Adhariani (UNIVED Press, 2026)
This study employs a qualitative case study approach on PT NLO, a logistics forwarding company whose revenue and net asset value exceed the criteria of micro, small, and medium business entities (MSMEs). PT NLO previously experienced a detrimental export activity. The research aims to provide comprehensive recommendations to PT NLO’s Management for the implementation of risk management in accordance with ISO 31000:2018. Data sources were obtained through observation, document analysis, and interviews with six informants. The analytical techniques applied include qualitative descriptive analysis, quantitative analysis, and thematic analysis. Recommendations were formulated using the Decision-Making Concept (Adair, 2019). The reasons risk management has not yet been implemented include human resource constraints, a focus on profit generation, and minimal regulatory enforcement. Based on an assessment of the external environment, all PESTEL components were identified to have the potential to reduce profit and net income. Internal environmental dynamics, derived from the Financial Ratio analysis for the period 2020–2024, indicate that financial performance has tended to remain stagnant. In terms of risk management understanding, key risks for PT NLO were identified for risk assessment according to the activity cycle. Operational, compliance, and financial risks were found to significantly affect business continuity. Management acknowledges the importance of risk management and has approved the establishment of a Task Force. With the establishment of a Risk Management Task Force, PT NLO is expected to be better prepared to address challenges from both external and internal environments and to conduct the risk management process in a structured manner.